2007
DOI: 10.1097/01.tp.0000261710.53848.51
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Kidney Transplantation From Nonheart-Beating Versus Heart-Beating Cadaveric Donors

Abstract: NHB donors carry the potential of expanding the cadaveric kidney pool. Although, transplants from NHB donors are associated with a greater incidence of early adverse events, long-term outcomes appear comparable with those of transplants from HB donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 24 publications
7
49
2
3
Order By: Relevance
“…The DCD grafts in this study by all accounts appeared to have been of high quality, predominantly having short warm ischemia time and coming from younger donors. This finding was unexpected because late graft loss in DCD kidney transplants has not been described in adult recipients (5)(6)(7)(8)(9)(10)(11)(12), nor was it identified in a previous analysis of pediatric recipients (15). Our ability to detect this difference is likely due to a substantial increase in power (from 26 DCD recipients in the previously largest study to 137 DCD recipients in this study) and follow-up time.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The DCD grafts in this study by all accounts appeared to have been of high quality, predominantly having short warm ischemia time and coming from younger donors. This finding was unexpected because late graft loss in DCD kidney transplants has not been described in adult recipients (5)(6)(7)(8)(9)(10)(11)(12), nor was it identified in a previous analysis of pediatric recipients (15). Our ability to detect this difference is likely due to a substantial increase in power (from 26 DCD recipients in the previously largest study to 137 DCD recipients in this study) and follow-up time.…”
Section: Discussionmentioning
confidence: 53%
“…In adults, DCD kidneys seem to result in similar graft and patient survival compared with donation after brain death (DBD) kidneys (5)(6)(7)(8)(9)(10)(11)(12). However, DCD kidneys also have a significantly higher rate of delayed graft function (DGF) compared with DBD kidneys (5,(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…DCD grafts, however, are exposed to significantly more ischemia-reperfusion injury than organs derived from donation after brain death. Previous studies have reported a threefold to fourfold higher risk of delayed graft function (DGF) with DCD kidneys as compared to kidneys from donation after brain death donors (DBD) (1,2). Primary nonfunction also occurred more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Primary nonfunction also occurred more frequently. Initial graft survival of DCD kidneys is generally inferior, but becomes comparable to DBD grafts at 5 years and 10 years after transplantation (2,3). The most obvious approach to minimize ischemia-reperfusion injury would be to keep warm ischemia time as short as possible and to limit cold ischemic time.…”
Section: Introductionmentioning
confidence: 99%